The Impact of Personal Hygiene Practices on the Incidence of Vaginal Discharge Among Adolescent Girls at Junior High School 29 Surabaya, 2023 - Siti Nur Aini, Rani; Kurniawati, Eighty Mardiyan; Utomo, Budi (Universitas Airlangga, 2025)
The teenage years are a period of rapid growth and development. Adolescence is a period of rapid growth and development, especially in the reproductive system. Many teenagers do not receive adequate knowledge about how to care for their reproductive organs because it is still considered taboo, so some teenagers may experience problems with their reproductive organs. A common issue faced by teenagers is leucorrhea. Leucorrhea is one of the problems that can arise due to the lack of knowledge among teenagers about maintaining reproductive health. Leucorrhea can develop into a serious problem if the care of the reproductive organs is not appropriately managed. This observational analytical study utilizes quantitative methods with a cross-sectional research design. The population was female Junior High School (SMPN) students 29 Surabaya. The sample was selected using purposive sampling. Data analysis employed univariate and bivariate methods, with the Chi-Square Test used for statistical analysis. The findings indicated that 78.8% of respondents experienced physiological vaginal discharge, 17.7% had pathological vaginal discharge, and 3.5% reported never having vaginal discharge. Statistical analysis revealed a significant relationship between personal hygiene and the incidence of vaginal discharge, with a p-value of 0.001. The research demonstrated a clear relationship between personal hygiene and the incidence of vaginal discharge. Educating adolescents about reproductive health and proper care for reproductive organs can help reduce the incidence of vaginal discharge among girls.